Respuesta :

Kazzin
[tex](2a^3)(5a^4)[/tex]
With this, you multiply the coefficients first, (2)(5)=10
Then when you multiply the variables, you add the exponents, [tex](a^3)(a^4)=(a^(^3^+^4^))=a^7[/tex]

So you would end up with: [tex]10a^7[/tex]

Answer: 10[tex]a^{7}[/tex]

Step-by-step explanation: Think of this problem of having two parts. The coefficients 2 and 5 and the powers [tex]a^{4}[/tex] and [tex]a^{7}[/tex]. To multiply these two terms together, simply multiply their coefficients and we have to add the exponents because we are multiplying powers.

2 × 5 = 10

[tex]a^{3}[/tex] × [tex]a^{7}[/tex] = [tex]a^{10}[/tex]

Therefore, our answer is 10[tex]a^{7}[/tex].